2011
DOI: 10.1016/j.aquaculture.2011.01.047
|View full text |Cite
|
Sign up to set email alerts
|

Histological and bacteriological changes in intestine of beluga (Huso huso) following ex vivo exposure to bacterial strains

Abstract: In the present study the intestinal sac method (ex vivo) was used to evaluate the interactions between lactic acid bacteria and staphylococci in the gastrointestinal (GI) tract of beluga (Huso huso). The distal intestine (DI) of beluga was exposed ex vivo to Staphylococcus aureus, Leuconostoc mesenteroides and Lactobacillus plantarum. Histological changes following bacterial exposure were assessed by light and electron microscopy. Control samples and samples exposed only to Leu. mesenteroides and a combination… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(40 citation statements)
references
References 44 publications
1
36
0
Order By: Relevance
“…Regarding the good growth of carp larvae fed Artemia or phosphatidylcholine-enriched diets (Geurden et al, 1998), result showed the decrease of enterocyte height was not due to underfeeding conditions, and it might be because of active lipid absorption with diffuse appearance. Salma et al, (2011) reported about the histological changes in intestine of beluga (Husohuso) by exposure of two different bacterial strains. Similarly in the current experiment, alterations were observed in the height of epithelial cells.…”
Section: Histoarchitecture Of the Intestine Of L Vannameimentioning
confidence: 99%
“…Regarding the good growth of carp larvae fed Artemia or phosphatidylcholine-enriched diets (Geurden et al, 1998), result showed the decrease of enterocyte height was not due to underfeeding conditions, and it might be because of active lipid absorption with diffuse appearance. Salma et al, (2011) reported about the histological changes in intestine of beluga (Husohuso) by exposure of two different bacterial strains. Similarly in the current experiment, alterations were observed in the height of epithelial cells.…”
Section: Histoarchitecture Of the Intestine Of L Vannameimentioning
confidence: 99%
“…Hence, we can infer that OKGM doses up to 2000 mg/kg influence the flora of the entire intestine similar to the effects of the 8000 mg/kg dose group. PCR-DGGE was used to analyze the intestinal flora, similar to previous reports (Yang et al 2007;Bjornsdottir et al 2009;Hermannsdottir et al 2009;Salma et al 2011;Kim and Kim 2013). Cultivation-based methods detected Vibrio sp., Pseudomonas sp., Janthinobacterium sp., Acinetobacter sp., and Photobacterium phosphoreum, whereas the direct DNA extraction approach found Lactobacillus fermentum, Lactococcus sp., P. phosphoreum, and Bacillus sp.…”
Section: Discussionmentioning
confidence: 99%
“…The result of LAB exposure to the intestine is of high importance as translocation and cell damage have been proposed as important criteria when evaluating the use of probiotics in endothermic animals as well as in fish [16,17]. Recently, the effect of ex vivo LAB exposure on the gut microbiota in fish was documented [13][14][15], but to the authors' knowledge the effect of prebiotic supplementation and ex vivo LAB exposure of the fish intestine has not been investigated.…”
Section: Discussionmentioning
confidence: 99%
“…The ex vivo intestinal sack method has been used in several studies to evaluate possible histological changes in the fish intestine after exposure to high levels of LAB [9,11,[13][14][15]. The result of LAB exposure to the intestine is of high importance as translocation and cell damage have been proposed as important criteria when evaluating the use of probiotics in endothermic animals as well as in fish [16,17].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation